The Integrated Density of States for an Interacting Multiparticle Homogeneous Model and Applications to the Anderson Model - Frédéric Klopp; Heribert Zenk (Advances in Mathematical Physics)
For a system of 𝑛 interacting particles moving in the background of a “homogeneous” potential, we show that if the single particle Hamiltonian admits a density of states, so does the interacting 𝑛-particle Hamiltonian. Moreover, this integrated density of states coincides with that of the free particle Hamiltonian. For the interacting 𝑛-particle Anderson model, we prove regularity properties of the integrated density of states by establishing a Wegner estimate.